Positioning of white oat cultivars for organic cultivation in Brazil and Paraguay - Ivan Ricardo (REVISTA DE AGRICULTURA, 2026)
This work aimed to position white oat cultivars for the organic system and determine the adaptability and stability of white oat for the organic system located in the states of Paraná, Rio Grande do Sul and Paraguay. Nine white oat genotypes were evaluated in 11 environments during five agricultural years, totaling 22 environments. The experimental design used was randomized blocks, arranged in four replications. The GGE model was used in order to reproduce inferences about the performance of genotypes and environments. Based on the best unbiased linear predictor, the genotypes IPR Artêmis, URS Taura, URS Poente, URS Altanera and URS Olada show high grain yield. Given the environments studied, Três Passos-RS and Ijuí-RS enhance the grain yield of white oats in an organic system. The genotypes URS Poente, URS Olada and URS Altanera were characterized as ideas based on superior performance in Palotina- PR, Três Passos - RS and Entre Rios do Oeste- PR.